Water Quality Evaluation of the Springs in Fernando de Noronha Island - Suzana M. G. L. Montenegro; Abelardo A. A. Montenegro; Valdinete Lins da Silva; Maurício Alves da Motta Sobrinho; Marcus Metri Correa (Revista Ambiente & Água, 2008)
The Fernando de Noronha archipelago is composed by 21 islands. The biggest of them, the Fernando de Noronha island, is supplied in domestic water by two reservoirs, one rain-water collecting system and another system using sea water desalinization. In addition, this island is supplied by water from six secondary artificial ponds and some wells and springs. However, during the summer drought time, the island endures a water supply reduction that endangers the touristic activities, which are the main economical local financial source. In this concern, were evaluated the quality of the water from several sources for human supplying. Some measurements were performed “in site” and laboratory physical chemical analyses as well. It could be concluded that a further reorganization of the water supply system ought to be carried out in order to avoid future problems and risk of water supply collapse in this island.